10(t-4)+5t=5(3t+4)-9

Simple and best practice solution for 10(t-4)+5t=5(3t+4)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(t-4)+5t=5(3t+4)-9 equation:


Simplifying
10(t + -4) + 5t = 5(3t + 4) + -9

Reorder the terms:
10(-4 + t) + 5t = 5(3t + 4) + -9
(-4 * 10 + t * 10) + 5t = 5(3t + 4) + -9
(-40 + 10t) + 5t = 5(3t + 4) + -9

Combine like terms: 10t + 5t = 15t
-40 + 15t = 5(3t + 4) + -9

Reorder the terms:
-40 + 15t = 5(4 + 3t) + -9
-40 + 15t = (4 * 5 + 3t * 5) + -9
-40 + 15t = (20 + 15t) + -9

Reorder the terms:
-40 + 15t = 20 + -9 + 15t

Combine like terms: 20 + -9 = 11
-40 + 15t = 11 + 15t

Add '-15t' to each side of the equation.
-40 + 15t + -15t = 11 + 15t + -15t

Combine like terms: 15t + -15t = 0
-40 + 0 = 11 + 15t + -15t
-40 = 11 + 15t + -15t

Combine like terms: 15t + -15t = 0
-40 = 11 + 0
-40 = 11

Solving
-40 = 11

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 6.4=0.8x | | 0.50x+0.05(18-x)=0.10(90) | | (3-w)(2w+1)=0 | | 8(4x-10)-4=76 | | (6-3-x)-2x=14 | | 5.8q-4.9-7.7q=-2.3-1.9q-2.6 | | -4+-10(-2-2j)+-8j= | | 5.2x-4=4.2x | | -w^2-7w+30= | | 3x+5y=1600 | | 3x+5y-1600=0 | | -v^2-5v+14= | | 2h+5(-8h+-10)= | | 2-3/4(5)+6=40 | | -v-5v+14= | | y-y-2y=0 | | 8x+8-9x+4=7x-8x-5 | | 8x+4=4+8x | | 0.375-x=6.625 | | 2x=9+2x+4 | | -.6666x=6 | | 5(4x-5)+3(18-5x)=2(2x+3)-2 | | -9x+-8(5x^2+-5)+6x^2= | | 6x^4y^2-15x^3y^3=0 | | -3(6p+5)-2(4-17p)=3(8+5p) | | 7(3x-4)-7=70 | | .24x-.2=.14x+1-.5x | | 5x-24=-32+9x | | 2x-1y=-34 | | 24x^2+62x+14= | | -9(-4v+4)+-3v+-6= | | (y-2)(y-1)=2(y-2)(y-3) |

Equations solver categories